2015
DOI: 10.1016/j.jtusci.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity and gas chromatography–mass spectroscopy analysis of Acacia karoo and Ziziphus mauritiana extracts

Abstract: The aim of the study was to identify the chemical ingredients and to evaluate the antibacterial activity of crude extracts of locally grown Acacia karoo and Ziziphus mauritiana. Antibacterial activity was measured by the agar well diffusion method, and chemical ingredients were identified by gas chromatography-mass spectrometry. Qualitative analysis of crude organic extracts confirmed the presence of high-and low-molecular-mass compounds. The extracts had a broad spectrum of antibacterial activity. An ethyl ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…Its presence as a major phytochemical compound was also in concordance with other studies on chloroformic extract of Acacia karoo root and Artemisia lavandulaefolia essential oil, where Bicyclo[2.2.1]heptan-2-one,1,7,7-trimethyl-, (1S)-was present as a major bioactive phytochemical constituent [56][57].…”
Section: Discussionsupporting
confidence: 90%
“…Its presence as a major phytochemical compound was also in concordance with other studies on chloroformic extract of Acacia karoo root and Artemisia lavandulaefolia essential oil, where Bicyclo[2.2.1]heptan-2-one,1,7,7-trimethyl-, (1S)-was present as a major bioactive phytochemical constituent [56][57].…”
Section: Discussionsupporting
confidence: 90%
“…Oxime-, methoxyphenyl, and hexadecanoic acid possess antioxidant and antimicrobial behaviour [51,52]. e compounds cyclotrisiloxane, hexamethyl, and isopropyl myristate have the antioxidant potential [53,54]. Undecane has a broad spectrum of antimicrobial activities [55].…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Inhibition of biofilms by ethanolic extract of Chlorella has hence provided an attractive anti-biofilm strategy against P. aeruginosa, which can be resistant to multiple antibiotic agents. The GC MS analysis revealed that Diethyl phthalate at Rt 15.563 (39.28%) and Trimethyl (4-tertbutyl phenoxy) silane at Rt 31.944 (25.63%), as the major compound in the ethanolic extract of Chlorella vulgaris which have been reported to have antibacterial activity 13,14 . The estimation of in-vitro maximal cytotoxic free concentration was done on vero cell line.…”
Section: Discussionmentioning
confidence: 99%